Partial sequence analysis and relative expression of the HSP70 gene of Vasconcellea pubescens - Fabio Marcelo Idrovo Espín; Tiffany Cevallos Vilatuña (Universitas Scientiarum)
Environmental factors affect nearly all land areas on the planet. Global warming is one of the most destructive of these factors because it has adverse effects on crop production systems. Plants are sessile organisms that have evolved complex mechanisms to cope with stress factors. Heat shock proteins (HSPs) are one of those mechanisms. In this study, we analyzed a partial gene sequence that encodes for HSP70 protein in Vasconcellea pubescens. We also measured the relative expression of the gene in plantlets of Vasconcellea pubescens and performed biochemical assays under heat stress. The plantlets were exposed to three temperatures 25° C (control), 45 °C and 55 °C (stress temperatures) for 4 hours. The bioinformatic analysis led to the first description of a partial sequence of the HSP70 gene and its evolutionary history in V. pubescens. We found significant differences for relative expression of the HSP70 gene, percentage of electrolyte leakage, and proline content between plants subjected to heat stress and those in the control group. Our results showed that V. pubescens displays thermotolerance even under extreme temperatures. V. pubescens is a poorly studied species that may contain genes of biotechnological interest (such as HSP70) that could be used for plant genetic modification.